1986
DOI: 10.1002/pssb.2221340145
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and thickness dependence of electrical and thermal transport coefficients of Bi1–xSbx films in an anisotropic, non‐degenerate two‐band model

Abstract: The thickness and temperature dependences of electrical and thermal transport coefficients (e.g. electrical conductivity, thermoelectric power, thermal conductivity) of Bil -,Sb, films are described by a non-degenerated two-band model, considering the anisotropic elliptical band structure (manyvalley model) of bulk Bil -,Sb,. The transport coefficients are measured in the temperature range 80 to 400 K on films with thicknesses 20 to 400 nm and the results are interpreted and discussed using the deduced relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…As indicated by Hoffman et al [24], due to the additional scattering at the sample surface, ordinary size effect (increase in resistivity) is seen when the mean free path of the charge-carrier (about 0.6 μm for Bi at room temperature [24]) is comparable with or greater than the sample thickness (about 25 nm). Comparing our results with those of the literature for similar film thickness, the electrical resistivity is of the same order but higher than most of the previous investigations [23,[31][32][33][34][35]. Boffoué et al [35] also observed the higher resistivity of bismuth films grown by PLD, and attributed this phenomenon to the low deposition temperature and the absence of post annealing.…”
Section: Electrical Propertiessupporting
confidence: 83%
“…As indicated by Hoffman et al [24], due to the additional scattering at the sample surface, ordinary size effect (increase in resistivity) is seen when the mean free path of the charge-carrier (about 0.6 μm for Bi at room temperature [24]) is comparable with or greater than the sample thickness (about 25 nm). Comparing our results with those of the literature for similar film thickness, the electrical resistivity is of the same order but higher than most of the previous investigations [23,[31][32][33][34][35]. Boffoué et al [35] also observed the higher resistivity of bismuth films grown by PLD, and attributed this phenomenon to the low deposition temperature and the absence of post annealing.…”
Section: Electrical Propertiessupporting
confidence: 83%
“…This non‐monotonic behavior has been described also using classical size effects based on the models of Fuchs, Mayadas and Dingle, considering the scattering of charge carriers at the surface and at grain boundaries. [ 24–28,61 ] In the case of nanowire arrays and networks, due to the high density of contacted nanowires, the electrical resistance values of the networks are very small (≈μohm), significantly smaller than the resistances of cables and/or contacts (≈mohm). In addition, since the exact number of connected wires is unknown, only relative values with respect to the resistance at 280 K can be provided.…”
Section: Resultsmentioning
confidence: 99%
“…Several years ago, Völklein et al published an extensive experimental study on Bi 1−x Sb x thin films with varying stoichiometry and thickness, in order to investigate their influence on the band structure and thermoelectric properties [23][24][25]. The results have been discussed in the framework of a previously proposed anisotropic non-degenerate two-band model, which can be found here [26]. Next to the unique thermoelectric behavior, recent investigations of nanostructured Bi 1−x Sb x alloys highlighted some further important topics like the experimentally investigation of topological insulators [27,28], possible revelation of a three-dimensional Dirac semimetal [29] or charge quantum Hall fractionalization [30].…”
Section: Introductionmentioning
confidence: 93%